Genome-Wide Analysis of TIR-NBS-LRR Gene Family in Potato Identified StTNLC7G2 Inducing Reactive Oxygen Species in Presence of Alternaria solani - Dubey, Namo; Chaudhary, Anjali; Singh, Kunal (Frontiers in Genetics, 2022)
Resistance gene analogs (RGAs) comprising NBS-LRR gene family members are considered prominent candidates in development of disease resistant genotypes. NBS-LRR gene family comprised of very large number of genes, therefore, members of one sub-family TIR-NBS-LRR (TNL) are identified in the present study from Solanum tuberosum genome, followed by their bioinformatics characterization. The study identified a total of 44 genes encoding 60 TNL transcripts with two prominent clusters at chromosome 1 and chromosome 11. Expression analysis of 14 TNL genes after Alternaria solani infection at 1, 2, 3, 5 and 7 days post inoculation in two disease tolerant varieties, Kufri Jyoti and Kufri Pukhraj and one relatively susceptible variety, Kufri Chandramukhi showed differential expression of many genes including high expression (>15 fold) of StTNLC6G2T1, and StTNLC11G9T1. Functional characterisation of one such gene, StTNLC7G2 reveal involvement in generation of reactive oxygen species under Alternaria solani attack, implicating its putative role in plant defense via hypersensitive response.